Application of sequence-based methods in human microbial ecology - Weng, Li; Rubin, Edward M.; Bristow, James

(untitled) (Genome Research, 2006)
Ecologists studying microbial life in the environment have recognized the enormous complexity of microbial diversity for many years, and the development of a variety of culture-independent methods, many of them coupled with high-throughput DNA sequencing, has allowed this diversity to be explored in ever-greater detail. Despite the widespread application of these new techniques to the characterization of uncultivated microbes and microbial communities in the environment, their application to human health and disease has lagged. Because DNA-based techniques for defining uncultured microbes allow not only cataloging of microbial diversity but also insight into microbial functions, investigators are beginning to apply these tools to the microbial communities that abound on and within us, in what has aptly been called “the second Human Genome Project.” In this review we discuss the sequence-based methods for microbial analysis that are currently available and their application to identify novel human pathogens, improve diagnosis of known infectious diseases, and advance understanding of our relationship with microbial communities that normally reside in and on the human body.